Loneliness and the COVID-19 pandemic: implications for intimate partner violence survivors - Goodman, Lisa A. (Journal of family violence, 2022)
The COVID-19 pandemic has dramatically highlighted the isolation of domestic violence survivors, triggering media coverage and innovative efforts to reach out to those who are trapped in their homes, facing greater danger from their partners than from the virus. But another harmful aspect of this difficult time has received far less attention: survivors’ intensified loneliness. Although loneliness can be catalyzed by isolation, it is a distinct psychological phenomenon that is internal and subjective in nature. Loneliness is not only acutely painful in its own right; it also inflicts a range of long lasting, health-related harms, and heightens survivors’ vulnerability to violence, creating a vicious cycle that may continue long after strict stay-at-home and physical distancing policies end. This may be particularly true for marginalized survivors, for whom larger structural inequalities and institutional failures compound the negative impact of loneliness. This brief report describes what we know about the nature and costs of survivor loneliness and uses the COVID-19 pandemic as a lens through which to review the ways current DV interventions may help alleviate loneliness (as distinct from isolation), and how these might be expanded to enhance survivor wellbeing, immediately and even after a return to “normal.”